PERANCANGAN ARENA E-SPORTS DI KOTA PALANGAKA RAYA - Amon Jon Seiber Elvinokio; Ngini, Giris; Harysakti, Ave (Jurusan Arsitektur UPR, 2024)
Palangka Raya City is a province in Central Kalimantan, has a large area and has experienced significant development in various fields. One of the important developments today is the popularity of online games or what are known as online games. Esports is a form of electronic sports that uses games as the main competition arena. In game competition, it is important to have a place to compete called Arena Esports. In Indonesia, the Esports industry is starting to develop and IeSPA is an Esports community that was just inaugurated by MENPORA. Indonesia has many talented young people in the field of Esports, and the government supports the development of Esports in this country. The Indonesian Esports (ESI) branch is still relatively new in Palangka Raya City, but has many fans, especially among young people. Therefore, the design of Arena Esports is expected to provide good playing and competition facilities, taking into account comfort, function, spatial planning, tournament facilities for participants and spectators, and using inspiration from living organisms with a Biomorphic Architecture approach.